2023
DOI: 10.1186/s42408-023-00175-6
|View full text |Cite
|
Sign up to set email alerts
|

Fuels change quickly after California drought and bark beetle outbreaks with implications for potential fire behavior and emissions

Abstract: Background An extreme drought from 2012–2016 and concurrent bark beetle outbreaks in California, USA resulted in widespread tree mortality. We followed changes in tree mortality, stand structure, and surface and canopy fuels over four years after the peak of mortality in Sierra mixed conifer and pinyon pine (Pinus monophylla) forests to examine patterns of mortality, needle retention after death, and snag fall across tree species. We then investigated how the tree mortality event affected surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 92 publications
1
3
0
Order By: Relevance
“…The pulsed increase in fine fuel loads from the MPB outbreak seems to be stabilizing (Figure 5A), but the coarse wood load was still increasing 10 years post‐outbreak and was much higher in 2022 in the control and Fire treatment relative to the Mech and Mech+Fire (Figure 5B). Studies of beetle‐killed ponderosa pines in the Southwest US and California have indicated low persistence of standing snags beyond 10 years (Chambers & Mast, 2014; Reed et al, 2023), which aligns with our findings of only approximately 21% of dead ponderosa pine still standing in 2020. Therefore, while the main fuel pulse from the outbreak is likely over, we expect that coarse fuel loading in the control and Fire treatment will continue increasing in the near future as many of these remaining snags fall.…”
Section: Discussionsupporting
confidence: 89%
“…The pulsed increase in fine fuel loads from the MPB outbreak seems to be stabilizing (Figure 5A), but the coarse wood load was still increasing 10 years post‐outbreak and was much higher in 2022 in the control and Fire treatment relative to the Mech and Mech+Fire (Figure 5B). Studies of beetle‐killed ponderosa pines in the Southwest US and California have indicated low persistence of standing snags beyond 10 years (Chambers & Mast, 2014; Reed et al, 2023), which aligns with our findings of only approximately 21% of dead ponderosa pine still standing in 2020. Therefore, while the main fuel pulse from the outbreak is likely over, we expect that coarse fuel loading in the control and Fire treatment will continue increasing in the near future as many of these remaining snags fall.…”
Section: Discussionsupporting
confidence: 89%
“…The percentage of brown-stage dead trees against the number of all dead trees (Methods) indicates areas with recency of mortality, which is relevant for indicating a potential ongoing mortality event, such as a burgeoning bark-beetle outbreak. This indicator is also relevant to fire risk modelling and fire behaviour forecasting because brown-stage trees are more likely to increase the risk for crown fires as compared to grey-stage dead trees, due to the presence of flammable low-moisture content foliage 17 , 49 , 50 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Compared with abiotic disturbances, biotic (e.g., insect pests or pathogens) disturbances are a longer process, and the impacts on forest ecosystems need to be validated through further studies [44]. Experimental plots and data on the intensity of different pest disturbances in the natural state are difficult to obtain; therefore, existing research on the disturbance of forest ecosystems with respect to biological factors (pests and pathogens) has focused on the aftermath of the large-scale forest mortality caused by pest disturbances [8,45,46], leading to a lack of studies on the disturbance of forests due to other biological factors and studies on forest disturbance processes in general. In this study, larch forests characterized by different levels of disturbance were selected as research objects, allowing for the further clarification of the soil changes occurring during forest death or decline.…”
Section: Soil Response To Bark Beetle Disturbancementioning
confidence: 99%
“…However, forests are currently being impacted by a wide range of disturbances globally, including changing wildfire regimes, biotic disturbances, and climate change [3][4][5], which have multiple impacts on biodiversity, ecosystem service function, and the carbon cycle [6]. For example, climate change-induced bark beetle outbreaks in countries such as Canada and the United States have led to widespread tree mortality [7,8]. Upon disturbance, the total amount of dead branches and Forests 2024, 15, 677 2 of 14 fallen logs on the forest floor increases, resulting in greater carbon inputs to the soil, thus affecting the nutrient and microbial composition of the soil [9].…”
Section: Introductionmentioning
confidence: 99%